2016
DOI: 10.1111/trf.13920
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell alloimmunization in patients with sickle cell disease: correlation with HLA and cytokine gene polymorphisms

Abstract: Brazilian SCD patients with the TNFA, IL1B, and HLA-DRB1 gene polymorphisms were at increased risk of becoming alloimmunized by RBC transfusions. These findings may contribute to the development of future therapeutic strategies for patients with SCD with higher susceptibility of alloimmunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 87 publications
4
64
0
3
Order By: Relevance
“…The incidence of alloimmunization in patients with SCD in Brazil ranges from 10 to 60% depending on the region and on the protocol of antigen matching used [4,5,6,7,8]. Even though our population is very mixed, we have observed that patients and donors exhibit differences in their genotype frequencies what could explain the high rates of alloimmunization in some regions [4,7].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The incidence of alloimmunization in patients with SCD in Brazil ranges from 10 to 60% depending on the region and on the protocol of antigen matching used [4,5,6,7,8]. Even though our population is very mixed, we have observed that patients and donors exhibit differences in their genotype frequencies what could explain the high rates of alloimmunization in some regions [4,7].…”
Section: Introductionmentioning
confidence: 82%
“…In previous studies, we found that TNFA -308A, IL1B -511T, RHAG 808G>A and HLA-DRB1*15 alleles may predict a good responder phenotype [8] and that RHAG 808G>A and HLA-DRB*15 alleles are closely linked to RH alloimmunization [8,22]. These findings contributed to the development of a transfusion strategy for non-alloimmunized SCD patients as typing for these polymorphisms could potentially help in the classification of responder and non-responder SCD patients, allowing blood with high level of compatibility to be transfused to responders in order to avoid production of RBC antibodies and the negative consequences of alloimmunization.…”
Section: Antigen-matched In Sickle Cell Disease Patients: Chancesmentioning
confidence: 99%
“…Identifying molecular markers to predict RBC alloimmunization relies on the fact that <20% of the transfusion recipients have the ability to develop alloantibodies after antigen‐mismatched transfusions (Higgins & Sloan, )and that patients’ genetic background is an important factor driving this susceptibility (Dinardo et al., ; Sippert et al., ). Our study is the first to evaluate the role played by polymorphisms on CTLA‐4 co‐stimulatory molecule on the alloimmunization scenario, demonstrating the association between ‐318C/T polymorphism, which modifies the expression of CTLA‐4 molecule on the cell surface, and the risk of post‐transfusion antibody development.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 21% of patients who have produced an RBC alloantibody produce additional alloantibodies after subsequent transfusion episodes . The genetic factors involved in RBC alloimmunization include HLA and non‐HLA genes . It should be noted that three of the four previously immunized patients had anti‐S antibodies, a specificity known to be frequently associated with multiple alloimmunization .…”
Section: Discussionmentioning
confidence: 99%